2021
DOI: 10.3748/wjg.v27.i4.358
|View full text |Cite
|
Sign up to set email alerts
|

Could saline irrigation clear all residual common bile duct stones after lithotripsy? A self-controlled prospective cohort study

Abstract: BACKGROUND A previous study showed that irrigation with 100 mL saline reduced residual common bile duct (CBD) stones, which potentially cause recurrent stones after endoscopic retrograde cholangiopancreatography. AIM To determine whether saline irrigation can improve CBD clearance after lithotripsy. METHODS This prospective self-controlled study enrolled patients receiving mechanical lithotripsy for large (> 1.2 cm) CBD stones. After occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“… 10 Our previous prospective self-controlled study of 47 patients who underwent lithotripsy and stone removal by ERCP found that although there were no stone residues on cholangiography, SpyGlass DS found that there were no stone fragments or biliary sludge residues in only 15% of the cases. 11 Taken together, the literature and our previous study show that cholangiography after endoscopic extraction does not detect residual stone fragments and biliary sludge. These tiny missed stone fragments become one of the reasons for stone recurrence.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“… 10 Our previous prospective self-controlled study of 47 patients who underwent lithotripsy and stone removal by ERCP found that although there were no stone residues on cholangiography, SpyGlass DS found that there were no stone fragments or biliary sludge residues in only 15% of the cases. 11 Taken together, the literature and our previous study show that cholangiography after endoscopic extraction does not detect residual stone fragments and biliary sludge. These tiny missed stone fragments become one of the reasons for stone recurrence.…”
Section: Introductionmentioning
confidence: 56%
“… 7 , 9 , 10 , 12 Our previous study confirmed that 94% of patients were free of stone fragments and biliary sludge after intermittent irrigation with 100 ml saline. 11 However, there are few reports about residual stone fragments and the recurrence of CBDS. Whether saline irrigation can reduce the recurrence of stones after endoscopic stone removal has not been confirmed by prospective randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the usual cases of bile duct stones without Roux-en-Y reconstruction, the recurrence rate of bile duct stones after endoscopic stone removal has been reported 4% - 24%. The incidence of residual stones after mechanical lithotripsy for intractable bile duct stones is 24%-40% [1] . In clinical practice, recurrent cholangitis due to residual bile duct stones occurs frequently even after endoscopic stone removal [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic treatment is now widely used as the first choice for bile duct stones [1] , [2] , [3] , [4] . With advances in endoscopic technology, endoscopists are actively challenging bile duct stone removal in patients who have undergone Roux-en-Y reconstruction or Billroth's operation II [5 , 6] .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, this may result in prolonged hospital stay in certain cases. According to statistics, the residual rate of stones can reach 12.9% ( 7 , 8 ). Several factors contribute to the residual of stones, including the presence of multiple stones, debris from lithotripsy, and other stone-related characteristics ( 9 ).…”
Section: Introductionmentioning
confidence: 99%